Bread Festival as a promoter of the knowledge, traditions, culture and tourism of the municipality of Mafra - Luís Silva, Adriana; Ventura Ramos, Elsa; Caldeira Heitor, João (European Public & Social Innovation Review, 2024)
Introduction: Mafra holds important resources which result in a very diversified tourist offer, strongly associated with its culture and traditions, and simultaneously endowed with contemporaneity and innovation. According to each theme, the resources can be aggregated into four large groups: history and culture; rurality and traditional culture; nature and environment; and coastline. The main objective of this study is to understand who are the visitors of the Bread Festival, their motivations and satisfaction, but also the different perceptions about the importance of the event in several variables for the municipality of Mafra, for visitors and participants/exhibitors. Methodology: bibliographical study of the various themes covered in the work and a questionnaire for visitors and participants/exhibitors at the Bread Festival. This was followed by an interview with the head of the Cultural Department of the municipality of Mafra. Results: For this, data were collected through a questionnaire to 755 visitors and 83 participants/exhibitors, applied from July 8 to 31, 2022, with the analysis being carried out using SPSS software, version 29, and Microsoft Excel software. Discussion: The aim is to infer various perspectives from the opinion of the sample, such as, for example, the influence of the Bread Festival on the promotion and dissemination of the traditions and culture of the municipality. Conclusion: It was possible to conclude that the event studied is of sublime importance for the conservation and enhancement of cultural traditions and the preservation of the identity and history of the municipality of Mafra.